2012
DOI: 10.1128/mbio.00489-12
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Transfer of Antibiotic Resistance Genes on Abiotic Touch Surfaces: Implications for Public Health

Abstract: Horizontal gene transfer (HGT) is largely responsible for increasing the incidence of antibiotic-resistant infections worldwide. While studies have focused on HGT in vivo, this work investigates whether the ability of pathogens to persist in the environment, particularly on touch surfaces, may also play an important role. Escherichia coli, virulent clone ST131, and Klebsiella pneumoniae harboring extended-spectrum-β-lactamase (ESBL) blaCTX-M-15 and metallo-β-lactamase blaNDM-1, respectively, exhibited prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 38 publications
3
112
0
1
Order By: Relevance
“…Horizontal transfer of plasmids does occur through conjugation, as illustrated by the transfer of extended-spectrum b-lactamase (CTX-M-15) and carbapenemase (NDM-1) plasmids between Enterobacteriaceae when dried on surfaces. 70,71 Furthermore, the mutation rate (the rate at which DNA replication mistakes occur during cell division) of bacteria in biofilms is increased. 6,72 Thus, both horizontal transfer of resistance determinants such as plasmids and increased mutation rates could result in the acquisition or denovo development of reduced susceptibility to antimicrobial agents and other important microbial capabilities, such as increased virulence.…”
Section: Transfer Of Plasmids and Development Of Antimicrobial Resistmentioning
confidence: 99%
“…Horizontal transfer of plasmids does occur through conjugation, as illustrated by the transfer of extended-spectrum b-lactamase (CTX-M-15) and carbapenemase (NDM-1) plasmids between Enterobacteriaceae when dried on surfaces. 70,71 Furthermore, the mutation rate (the rate at which DNA replication mistakes occur during cell division) of bacteria in biofilms is increased. 6,72 Thus, both horizontal transfer of resistance determinants such as plasmids and increased mutation rates could result in the acquisition or denovo development of reduced susceptibility to antimicrobial agents and other important microbial capabilities, such as increased virulence.…”
Section: Transfer Of Plasmids and Development Of Antimicrobial Resistmentioning
confidence: 99%
“…Copper alloys acting on abiotic surfaces showed that besides the rapid death of antibiotic resistant strains, it caused destruction of plasmid and genomic DNA, which has an implication in preventing the spread of infections and gene transfer (Warnes et al, 2013& Bagchi et al, 2013. Copper surfaces or their alloys are able to eliminate 99.9 % of pathogenic bacteria in hours, including methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli, Pseudomonas aeruginosa, Listeria monocytogenes, Salmonella enterica, Campylobacter jejuni, Legionella pneumophila, Clostridium difficile and Mycobacterium tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms will exploit an inadequately cleaned niche to exchange genetic material coding for antimicrobial resistance and other survival mechanisms (156)(157)(158). This could include resistance or tolerance to disinfectants.…”
Section: Contamination Of Cleaning Equipment and Liquidsmentioning
confidence: 99%